Characteristics of acoustic signals in healthy children using the new device "Trembita-Corona" - Khomych, Olha; Marushko, Yuriy (ScienceRise: Medical Science, 2023)
In 2016, the last revision of the nomenclature of breathing sounds took place at the Congress of the European Respiratory Society in Amsterdam. Purpose: to determine the features of the acoustic signal in healthy children using the new "Trembita-Corona" device. Materials and methods. 100 healthy children aged from 1 month to 18 years were examined. We have distinguished 3 main groups. The 1st research group included 700 acoustic signals that are characteristic of the vesicular type of breathing, the 2nd group - 100 acoustic signals that are characteristic of the tracheal type of breathing, the 3rd group - 200 acoustic signals that are characteristic of the bronchovesicular type of breathing. The results. With the help of the new "Trembita-Corona" device, a reference computerized database of acoustic signals for lung condition monitoring in healthy children was created. The parameters of the acoustic signal during different types of breathing in healthy children were formalized. Differences were found between the vesicular and the tracheal type of breathing in the average signal power in 0.1, 2, 3, 4, 5, 7, 8 and 9 octaves, in the frequency of the acoustic signal - in 0, 4, 5, 8 octaves, amplitude of the acoustic signal - in 0,3,4,5, 8 octaves. Differences between the vesicular and the bronchovesicular types of breathing were found in the average signal power in 0, 1, 2, 4, 5, 6, 7, 8 and 9 octaves, in the frequency of the acoustic signal - in 0, 3.5, 6 and 7 octaves, amplitude of the acoustic signal - in all 8 octaves. Conclusions. The "Trembita-Corona" acoustic monitoring device makes it possible to describe sound phenomena that normally occur in healthy children depending on the type of breathing based on the average signal power, amplitude and frequency of the acoustic signal in 11 octaves